2017
DOI: 10.1186/s12941-017-0236-7
|View full text |Cite
|
Sign up to set email alerts
|

Extended spectrum beta-lactamase and metallo beta-lactamase production among Escherichia coli and Klebsiella pneumoniae isolated from different clinical samples in a tertiary care hospital in Kathmandu, Nepal

Abstract: BackgroundExtended spectrum beta-lactamase (ESBL) and metallo beta-lactamase (MBL) production in Klebsiella pneumoniae and Escherichia coli are the commonest modes of drug resistance among these commonly isolated bacteria from clinical specimens. So the main purpose of our study was to determine the burden of ESBL and MBL production in E. coli and K. pneumoniae isolated from clinical samples. Further, the antimicrobial susceptibility patterns of E. coli and K. pneumoniae were also determined.MethodsA cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

51
74
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(144 citation statements)
references
References 19 publications
51
74
19
Order By: Relevance
“…However, our result was lower than studies done in Sierra Leone (85.7 %) [24], Gondar (87.4%) [16], Bahir Dar (93.1%) [28], Nepal (96.8%) [29].The difference in magnitude of MDR isolates might be due to patient condition, definition for MDR and empirical treatment trend. In addition, our result was higher when compared to a previous study done in Jimma (59.3%) [30], Nepal (54.2%) [27], another study in Nepal by Lamichhane et al [31] reported (33.14%). However, the increased proportion of MDR seen in this study was considered as alarming because only a few treatment options remain for infections.…”
Section: Multi Drug Resistance Pattern Of Gram Negative Bacillicontrasting
confidence: 85%
See 1 more Smart Citation
“…However, our result was lower than studies done in Sierra Leone (85.7 %) [24], Gondar (87.4%) [16], Bahir Dar (93.1%) [28], Nepal (96.8%) [29].The difference in magnitude of MDR isolates might be due to patient condition, definition for MDR and empirical treatment trend. In addition, our result was higher when compared to a previous study done in Jimma (59.3%) [30], Nepal (54.2%) [27], another study in Nepal by Lamichhane et al [31] reported (33.14%). However, the increased proportion of MDR seen in this study was considered as alarming because only a few treatment options remain for infections.…”
Section: Multi Drug Resistance Pattern Of Gram Negative Bacillicontrasting
confidence: 85%
“…In the present study, the overall magnitude of MDR among all GNB isolate was 73.7%. There were also similar findings from studies conducted in Gondar (68.0%) [25], Dessie (74.6%) [26], Debre Markos: (72.2%) [21] and Nepal (64.0%) [27]. However, our result was lower than studies done in Sierra Leone (85.7 %) [24], Gondar (87.4%) [16], Bahir Dar (93.1%) [28], Nepal (96.8%) [29].The difference in magnitude of MDR isolates might be due to patient condition, definition for MDR and empirical treatment trend.…”
Section: Multi Drug Resistance Pattern Of Gram Negative Bacillisupporting
confidence: 84%
“…We observed 17.5% of the Escherichia coli and 21% of Klebsiella pneumoniae to be ESBL producers. In our study, both cefotaxime-clavulanic acid and ceftazidimeclavulanic acid identified ESBL producers equally, whereas in other studies cefotaxime-clavulanic acid identified more number of ESBL producers compared to ceftazidime-clavulanic acid [19,21,22]. ESBL strains apart from being resistant to third generation cephalosporins also showed more than 50% resistance to ampicillin/sulbactum, amikacin, gentamcin, ofloxacin and cotrimoxazole.…”
Section: Discussioncontrasting
confidence: 52%
“…We also aimed to identify risk factors related to food. We focused on the recent five years because of the increasing prevalence of multiple mechanisms of resistance among Gramnegative bacteria causing extraintestinal and intestinal infections during this period, including mechanisms such as ESBL [25,26], carbapenemase [27], and metallo-betalactamase production [26], and plasmid-mediated colistin resistance [28].…”
Section: Introductionmentioning
confidence: 99%